Co3O4 microtubules derived from a biotemplated method for improved lithium storage performance. Issue 12 (15th August 2017) - Yan, Dongliang; Zhang, Ying; Zhang, Xiuyun; Yu, Zhaozhe; Zhao, Yunyun; Zhu, Guisheng; Chen, Guangcun; Ma, Chuanguo; Xu, Huarui; Yu, Aibing
Abstract: A simple and effective biotemplated method is applied to fabricate porous microtubular cobalt oxide by infiltration of cotton fiber with a cobalt nitrate solution, followed by annealing at 500 °C in air. The as-obtained Co3 O4 have been characterized by: X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), N2 adsorption and desorption measurements, and thermal analysis (TG). According to these results, the as-prepared Co3 O4 display a perfect tubular morphology and mesoporous features. The electrochemical performance of the as-obtained sample was studied for use as a lithium-ion battery anode material by cyclic voltammetry (CV), and charge-discharge and electrochemical impedance spectroscopy (ESI) measurements. Compared to bulk Co3 O4 and previously reported nanostructured Co3 O4 electrodes, mesoporous microtubular Co3 O4 show an improved lithium storage properties, which can be attributed to their unique morphology, large specific surface area and mesoporous feature.